2013
DOI: 10.1002/mds.25355
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical classification of tremor in elderly—A community‐based survey in Brazil

Abstract: Prevalence data on different types of tremor among the elderly population are very scarce. The objective of this study was to study the prevalence of tremor in a community-dwelling elderly population in the town of Bambuí, Brazil. The authors studied 1186 inhabitants aged≥64 years. This was a 2-phase study in which all participants who screened positive in a questionnaire for tremor and parkinsonism or who used drugs capable of causing/suppressing tremor were examined. In this population, the prevalence rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
24
0
5
Order By: Relevance
“…These studies were conducted with old individuals, and as far as we know, there is no study of enhanced PT prevalence in young individuals. Erer et al [13] found the enhanced PT prevalence 4.14% in individuals at the age of 40 or more [13], and Barbosa et al [12] found increased enhanced PT prevalence 2.8% in individuals at the age of 64 or more [12]. We reported the prevalence of detectable PT in normal individuals as 4.3% which is slightly higher than the prevalence of ET.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…These studies were conducted with old individuals, and as far as we know, there is no study of enhanced PT prevalence in young individuals. Erer et al [13] found the enhanced PT prevalence 4.14% in individuals at the age of 40 or more [13], and Barbosa et al [12] found increased enhanced PT prevalence 2.8% in individuals at the age of 64 or more [12]. We reported the prevalence of detectable PT in normal individuals as 4.3% which is slightly higher than the prevalence of ET.…”
Section: Discussionsupporting
confidence: 40%
“…The physiological tremor (PT) is defined as the postural tremor with low amplitude at classically [8][9][10][11][12] Hz frequency that may be seen in everybody and may increase with anxiety and fatigue [1,11]. Healthy people may show some tremor but this condition does not cause any complaint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…É possível que a exigência física ainda influencie nessa proporção. Em média, a idade dos trabalhadores portadores de tremor essencial foi de 51 anos, e está abaixo da média da maioria dos estudos que avaliam essa doença 8,9,11,37,41 . A precocidade da doença é um aspecto frequentemente encontrado em doenças ocupacionais.…”
Section: Discussionunclassified
“…Já a taxa de incidência foi estimada entre 23,7 e 616 por 100 mil 10 . Um estudo brasileiro realizado em uma cidade do interior de Minas Gerais observou uma prevalência de 7,4% de tremor essencial em indivíduos com ≥ 64 anos 11 .…”
Section: Cad Saúde Pública 2017; 33(8):e00194915unclassified